The Effect of Exclusive Breastfeeding on Stunting Prevention in Toddlers - Senja Artiningrum; C.Ermayani Putriyanti (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2021)
Stunting is a condition in which children experience growth failure that occurs during the fetal growth in the womb for up to 1000 first days of his/her life. This condition is very important because 1 of 3 children in Indonesia experience stunting. The effect of stunting is very wide for children's lives in the future, where children are easily infected and have poor cognitive development disorders and they could become the country burden in the future. Exclusive breasfeeding is vital, because breastmilk is the perfect food for babies. The purpose of this study was to determine the effect of exclusive breastfeeding on the incidence of stunting in toddlers. The method used is a literature review by referring to various research articles about breastfeeding and stunting. The databases used include Google Scholar, Digital Reference Garba and ProQuest. The result showed that there is significant effect between exclusive breastfeeding on stunting prevention in toddlers. It is suggested to do a health education or socialization about exclusive breastfeeding to adolescents, it is hoped that it can form a positive perception of adolescents as prospective parents about the benefits of exclusive breastfeeding including stunting prevention.